Transcolonic Perirectal NOTES Access (PNA): A feasibility study with survival in swine model - OLIVEIRA,ANDRÉ L.A. (2017)
ABSTRACT Transrectal access still has some unsolved issues such as spatial orientation, infection, access and site closure. This study presents a simple technique to perform transcolonic access with survival in a swine model series. A new technique for NOTES perirectal access to perform retroperitoneoscopy, peritoneoscopy, liver and lymphnode biopsies was performed in 6 pigs, using Totally NOTES technique. The specimens were extracted transanally. The flexible endoscope was inserted through a posterior transmural incision and the retrorectal space. Cultures of bacteria were documented for the retroperitoneal space and intra abdominal cavity after 14 days. Rectal site was closed using non-absorbable sutures. There was no bowel cleansing, nor preoperative fasting. The procedures were performed in 6 pigs through transcolonic natural orifice access using available endoscopic flexible instruments. All animals survived 14 days without complications, and cultures were negative. Histopathologic examination of the rectal closure site showed adequate healing of suture line and no micro abscesses. The results of feasibility and safety of experimental Transcolonic NOTES potentially brings new frontiers and future wider applications for minimally invasive surgery. The treatment of colorectal, abdominal and retroperitoneal diseases through a flexible Perirectal NOTES Access (PNA) is a promising new approach.